The The Importance of Considering the Different Learning Styles in Students of English as a Foreign Language - Zúñiga Hernández, María Patricia (2023)
This paper aims to consider the importance of implementing different learning styles with learners of English as a Foreign Language (EFL). In addition, information is provided on the existence of these learning styles as well as the importance of teachers’ implementation of them. Various academic articles were reviewed and compared to highlight the transcendence of the use of learning styles to favor the EFL teaching and learning process. In addition, some examples of activities that can be developed to promote them are suggested.